THE STRUCTURE AND FUNCTIONS OF FIGURATIVE COMPARISON IN A LITERARY TEXT - Sodiqova S.T. (Journal Park Publishing, 2022)
This article focuses on the structure and functions of comparison in a literary text. It also discusses differences between metaphor and figurative comparison (simile).
Keywords: text; figurative comparison; semantic